Exam Ref MS-500 Microsoft 365 Security Administration - Fisher, Ed; Chamberlain, Nate (Microsoft Press, 2020)
Prepare for Microsoft Exam MS-500: Demonstrate your real-world knowledge of Microsoft 365 security implementation and administration, including identity, access, threat and information protection, governance, and compliance. Designed for professionals with Microsoft security experience, this Exam Ref focuses on the critical thinking and decision-making acumen needed for success at the Microsoft 365 Certified:Security Administrator Associate level. Focus on the expertise measured by these objectives: Implement and manage identity and access Implement and manage threat protection Implement and manage information protection Manage governance and compliance features in Microsoft 365 This Microsoft Exam Ref: Organizes its coverage by exam objectives Features strategic, what-if scenarios to challenge you Assumes you have expertise implementing and administering security in a Microsoft 365 environment.